Cointegration and causality between macroeconomic variables and life insurance demand in India. Issue 4 (18th September 2017) - Mathew, Biju; Sivaraman, Sunitha
Abstract : Purpose: The purpose of this paper is to analyze the macroeconomic determinants of life insurance demand in India. The recent decline in life insurance activity calls for a study on the factors influencing life insurance demand in India. Design/methodology/approach: This study employs econometric techniques like augmented Dickey-Fuller test, Johansen cointegration test, vector error correction models and the Granger causality test to estimate the macroeconomic predictors of life insurance demand in India, during the period 1980-1981 to 2013-2014. Findings: Financial sector development and inflation positively influence life insurance demand in India. The real rate of interest and income are negatively related to life insurance consumption. The study finds an insignificant relation between the level of social security expenditure and life insurance buying. Financial sector development is found to Granger-cause life insurance demand. Research limitations/implications: Product-wise analysis of life insurance demand is not attempted due to lack of unit-level data. The impact of regulatory changes on life insurance demand in India is not attempted. Practical implications: Intervention by the policy makers is required to arrest the decline of life insurance activity in India. Efforts are required to widen the financial sector of the Indian economy to accelerate the growth of life insurance activity. Originality/value: The paper introduces a new measure of life insurance demand, the total regular new business premium, in the estimation of life insurance demand determination.